Choroidal detachment after trabeculectomy versus deep sclerectomy in myopic patients - Abdelhamed S Elhofi; Mohamed M Lolah (Delta Journal of Ophthalmology, 2017)
Purpose The aim of this study was to compare the prevalence of choroidal detachment after penetrating trabeculectomy (PT) versus nonpenetrating trabeculectomy (NPT) in glaucomatous myopic eyes. Patients and methods This is an interventional controlled randomized clinical study. The present study included 60 eyes with open-angle glaucoma, 30 of which underwent traditional PT with mitomycin C (MMC), whereas the other 30 eyes underwent NPT (deep sclerectomy collagen implant) with MMC. Results The mean postoperative intraocular pressure (IOP) in the PT group was significantly lower than that in the NPT group (P<0.0001). The occurrence of choroidal detachment was correlated with lower levels of IOP assessed 1 week after surgery (r=−0.664, P<0.0001) and consequently positively correlated with drop in IOP (%) after 1 week of surgery (r=0.67, P<0.0001). There was no significant difference between preoperative and postoperative best-corrected visual acuity in the PT group (P=0.278), whereas there was a significant difference between preoperative and postoperative best-corrected visual acuity in the NPT group (P=0.032). Postoperative shallowing of the anterior chamber was not observed in the NPT group, in contrast to the PT group, with a statistically significant difference (P=0.001). The prevalence of postoperative choroidal detachment in the NPT group was significantly lower than that in the PT group (P=0.008). Conclusion PT was found to be more effective compared with deep sclerectomy in lowering the IOP, especially with the use of MMC. The nonpenetrating technique with MMC is safer in avoiding hypotony complications and reducing the incidence of choroidal detachment, which occur significantly more frequently in myopic eyes.